Examining Spending Efficiency and Budget Realization Growth in Regional Financial Performance: A Study of West Java Province - Sofyan, Aldriantara; Nurjaman, Kadar; Joharudin, Agus (GoAcademica Research & Publishing, 2025)
This study examines the impact of spending efficiency ratio and budget realization growth ratio on the financial performance of the Regional Inspectorate of West Java Province from 2020 to 2023. The study employs a quantitative approach with multiple linear regression analysis to measure the effect of independent variables on financial performance. The findings indicate that the spending efficiency ratio has a positive and significant effect on financial performance, demonstrating that optimal budget utilization enhances regional financial stability. Additionally, the budget realization growth ratio also has a significant impact, although its influence is relatively lower than spending efficiency. The results emphasize the importance of efficient financial management and budget allocation planning in improving regional financial performance. These findings provide insights for policymakers to enhance financial transparency and accountability in local government budget planning and execution.